Variations of cyclotron resonant scattering features in Vela X-1 revealed with Insight-HXMT. Issue 2 (2nd June 2022) - Liu, Q; Wang, W; Chen, X; Ding, Y Z; Lu, F J; Song, L M; Qu, J L; Zhang, S; Zhang, S N
ABSTRACT: We present a detailed study of the high-mass X-ray binary Vela X-1, using observations performed by Insight-HXMT in 2019 and 2020, concentrating on timing analysis and spectral studies including pulse phase-resolved spectroscopy. The cyclotron line energy is found to be ∼21–27 and 43–50 keV for the fundamental and first harmonic, respectively. We present the evolution of spectral parameters and find that the two line centroid energy ratio E 2 / E 1 evolved from ∼2 before MJD 58900 to ∼1.7 after that. The harmonic cyclotron line energy has no relation to the luminosity but the fundamental line energy shows a positive correlation with X-ray luminosity, suggesting that Vela X-1 is located in the sub-critical accreting regime. In addition, the pulse phase-resolved spectroscopy in Vela X-1 is performed. Both the cyclotron resonant scattering feature and continuum parameters show strong variability over the pulse phase with the ratio of two line energies about 2 near the peak phases and down to ∼1.6 around off-peak phases. Long-term significant variations of the absorption column density and its evolution over the pulse phase may imply the existence of the clumpy wind structure near the neutron star.